Dependence of Cystatin C and NT-pro-BNP levels on intramyocardial tension of the left ventricle in patients with chronic heart failure - V.V. Syvolap; N.V. Tumanskaya; A.A. Popovych; L.M. Polyschuk (Patologìâ)
Abstract